2014
DOI: 10.1182/blood-2013-08-521419
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of anemia of inflammation: complex pathogenesis with partial dependence on hepcidin

Abstract: • An injection of heat-killedBrucella abortus in mice causes prolonged anemia with features similar to human anemia of inflammation.• Ablation of hepcidin ameliorates anemia of inflammation in this model and allows faster recovery.Anemia is a common complication of infections and inflammatory diseases, but the few mouse models of this condition are not well characterized. We analyzed in detail the pathogenesis of anemia induced by an injection of heat-killed Brucella abortus and examined the contribution of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
117
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 41 publications
7
117
2
1
Order By: Relevance
“…Accordingly, new rodent models of cancer (94) and infection (82,83) have been recently generated. These model systems will be essential for dissecting the more intricate interactions between hepcidin regulation and changes in iron homeostasis induced by inflammation or infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, new rodent models of cancer (94) and infection (82,83) have been recently generated. These model systems will be essential for dissecting the more intricate interactions between hepcidin regulation and changes in iron homeostasis induced by inflammation or infection.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, ERFE also appears to play a role in the recovery of organisms from the anemia of inflammation (81). Heat-killed Brucella abortus (HKBA) is known to induce an anemia of inflammation response in rodents (82,83). Mice lacking ERFE have both a more severe and a more prolonged anemia, and more greatly elevated hepcidin expression, as compared with wild type animals upon exposure to HKBA.…”
Section: Anemia Of Inflammation and Infectionmentioning
confidence: 99%
“…The mouse model of systemic inflammation induced by heat-killed Brucella abortus (BA) allows the study of recovery from inflammation-induced anemia in mice. [8][9][10][11] Mice exhibit a transient but severe anemia and elevated EPO levels 14 days after injection of BA followed by the suppression of hepcidin and partial recovery from anemia by 28 days. Wild-type (WT) mice injected with BA develop a very rapid inflammatory response associated with increased hepcidin production 6 hours after BA administration and present decreased serum iron concentration and transferrin saturation, typical of iron-restricted anemia.…”
mentioning
confidence: 99%
“…The role of hepcidin in AI is confirmed by the milder anemia and the faster recovery of mice lacking interleukin-6 or hepcidin compared with their WT counterparts. 10,11 We recently described the new erythroid factor erythroferrone (ERFE), which is responsible for early hepcidin suppression during erythropoietic activity stimulated by endogenous or exogenous EPO. 12 We showed that Erfe-deficient mice fail to suppress hepcidin after erythropoietic stimulation resulting in a significant delay in the recovery from hemorrhage-induced anemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation